Human Syngamosis as an Uncommon Cause of Chronic Cough - Pulcherio,Janaina Oliveira Bentivi (2013)
Introduction  Chronic cough may represent a diagnostic challenge. Chronic parasitism of upper airways is an unusual cause. Objective  To describe a case of human syngamosis as an uncommon cause of dry cough. Case Report  An endoscopic exam performed in a woman suffering of chronic cough revealed a Y-shaped worm in the larynx identified as Syngamus laryngeus. Discussion  This nematode parasitizes the upper respiratory tract of many animals including humans. The diagnosis is performed by the examination of the worm expelled by cough or by endoscopy. Endoscopic exam is easy to perform and is essential in the diagnosis of causes of chronic cough, even uncommon entities. Removal is the only efficient treatment.